Combined Antidiabetic and Antidyslipidemic Activity of Ageratum conyzoides and Gynura procumbens in Alloxan-induced Diabetic Rats - Yani Mulyani; Nazarul Mastura; Salsha Rosilopya; Aris Suhardiman; Kania Fajarwati; Entris Sutrisno (Majalah Obat Tradisional, 2023)
Unhealthy lifestyle habits greatly increase the risks of various degenerative illnesses, for example, diabetes mellitus as well as dyslipidemia. Recent studies have shown that the pharmaceutical drugs used for the treatment of these conditions have undesirable side effects. This indicates that it is necessary to find more effective and safe alternative treatment options, particularly in medicinal plants, such as Ageratum conyzoides and Gynura procumbens. Therefore, this research examined the combined antidiabetic and antidyslipidemic activity of Ageratum conyzoides and Gynura procumbens extracts in alloxan-induced diabetic rats. The insulin sensitivity of the test animals was assessed at the beginning of the experiment using the oral glucose tolerance test (OGTT) through the administration of 3Â g/kgBW glucose. Pancreatic destruction was induced with the intraperitoneal injection of a single dose of 150 mg/kgBW alloxan, and the rats were treated with ethanol extract for 14Â days. High-density lipoprotein cholesterol (HDL-C), Triglycerides (TG), total cholesterol (TC), and low-density lipoprotein cholesterol (LDL-C) were measured using the enzymatic method. The results showed that the single extracts and their combination exhibited high antidiabetic and antidyslipidemic activity. This was indicated by a substantial reduction in fasting blood sugar, TG, TC, and LDL-C (p<0.05), and an insignificant increase in HDL-C. The activity of the combined extract was similar to the single extracts, but it was not better in decreasing TG levels. Based on these findings, 95% ethanol extract of Ageratum conyzoides, Gynura procumbens, and their combination exhibited high antidiabetic and antidyslipidemic activity in alloxan-induced rats.